Amundsen versus Scott: Are growth paths related to firm performance? - Alex Coad; Sven-Olov Daunfeldt; Daniel Halvarsson (Institute of Retail Economics (HFI), 2020)
In the race to the South Pole, Roald Amundsen's expedition covered an equal distance each day, irrespective of weather conditions, while Scott's pace was erratic. Amundsen won the race and returned without loss of life, while Scott and his men died. We investigate how firms' sales growth deviate from the long-run average growth path. Our baseline results suggest that growth path volatility is associated with higher growth of sales and profits, but is also associated with higher exit rates. This is driven by firms with negative growth rates. For positive-growth firms, volatility is negatively associated with both sales growth and survival.
Keywords: D22; L25; L26; 330; Firm dynamics; Sales growth; Firm exit; Growth paths; Scale-up; Postentry growth